Agriculture-Nutritious Foods: Impact of Climate Change (Temperature and Precipitation) - Reddy, Sazzala Jeevananda (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2024)
Climate change is not global warming; it is only one component of climate change as defined by WMO/IPCC/UNFCCC. The two main climatic parameters that play vital role in agriculture production are temperature and precipitation. Temperature presents high seasonal and annual variations, which form irregular variations part under natural variability of climate change. Since, around the past two decades groups are polluting agriculture research under the disguise of global warming which is insignificant when compared to seasonal and annual variations. Agriculture is adopted to such vagaries. Countries like USA and Australia moving past to renewable energy but country like India, second most populous after China contributing to around 50% of thermal power production similar to USA; and USA and India contributing to around 25% of the nuclear and hydropower, respectively. The modern agriculture system from 1960, new seeds are tailored to chemical inputs and now genetically modified (GM) seeds entered India. In such scenarios, reports say that, the two major crops, namely, rice and wheat that are distributed under Public Distribution System (PDS). Reports also say that the strength and nutrition quality are reduced by 45% by now and will be reducing to 100% by 2040. According to FAO around 30% of what is produced is going as waste; but it is more than 40% for India excluding illegal exports; PDS rice entering black market. Another important factor is crops/vegetables/animals grow under polluted water: Needed experiences, best practices, and scalable solutions for the integration of biodiversity into agriculture. There are three systems according to technology. They are: Traditional Agriculture Technology-Traditional seeds under traditional organic inputs including Animal Husbandry in Agriculture system; Green Revolution Technology-Modern Seeds are tailored to chemical inputs under irrigation excluding animal husbandry in Agriculture System; GM Technology--Genetically modified seeds tailored to chemical inputs and irrigation excluding animal husbandry in Agriculture System; Moisture is the limiting factor for crop growth and production in tropical warm regions wherein most of the developing countries are located. Moisture availability varies with space and time in association with the natural variability in rainfall and snowfall that forms the principal component of the climate change. Droughts and floods are part of it. That is moisture availability varies with country to country, region to region within the country, and station to station within a region. This plays an important role in production during these two periods and are discussed. In addition, two issues related agri-foods and nutrients are discussed.